Models of integrated inventory system with stock-dependent demand / Hafizah Zulkipli - Zulkipli, Hafizah (2013)
This study is proposing two integrated inventory models by considering stockdependent demand. We presented a mathematical model where a vendor procures raw material in single/multiple instalment(s), processes them to make finished products, ships to single/multiple buyer(s) at single/multiple shipment(s) and stores them at the warehouse before presents at the display area with single/ multiple transfer(s). The first model operates with a single-vendor and a single-buyer by considering different shipment policies. Two types of shipment policies were considered in the first model: geometric shipment and geometricthen-equal shipment sizes. The optimum joint profits were obtained by using Wolfram Mathematica Version 7. Numerical examples were then presented for discussion. A numerical sensitivity analysis was conducted to investigate the reaction of the optimal total profit to the changes in the parameters value. The second model operates with a single-vendor and multiple buyers by considering equal shipment sizes. The total optimum profit and solution procedures were obtained by using Microsoft Excel Premium Solver Version 12.5 which can solve non-linear optimization problems. This procedure was used to analyze some numerical examples in order to examine the model's sensitivity to parameter changes as well.